DOOM SPENDING AMONG GENERATION Z: CONSUMER BEHAVIOR ANALYSIS AND ISLAMIC ECONOMIC PERSPECTIVE - Najib, M. Thoha Ainun; Silky Roudhotus Sa’adah (JSE: Jurnal Sharia Economica, 2026)
This research examines the phenomenon of doom spending among Generation Z, characterized by excessive spending as a response to stress and anxiety. It analyzes the application of Islamic economic principles to overcome this consumptive behavior through a qualitative approach with a case study method involving 25 respondents aged 18 to 25 years. Research finds that the leading causes of doom spending include academic stress, the influence of social media, and a lack of knowledge about financial management. The impacts of this behavior include mental health problems and economic difficulties. This research recommends Sharia-based financial education and awareness campaigns to increase understanding of the negative impacts of doom spending so that it is hoped that Generation Z can achieve better economic and mental well-being.